2006
DOI: 10.1007/s11459-006-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Foreign trade, environmental protection and sustainable economic growth in China

Abstract: Since the 1990s, China has exhibited growth in both foreign trade and the economy. Promoting environmental protection and sustainable economic growth are main concerns in the academic profession in the country. This paper makes an empirical analysis of trade and environmental pollution, and discusses the inherent relationship between foreign trade, environmental protection and sustainable economic growth. In addition, this paper makes several policy suggestions with a view to adjusting trade structure, enforci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Yang et al (2018) studied the impact of government governance on regional carbon emissions in China and discovered that the level of legal regulation and regional corruption had a strong negative effect on carbon reduction [22]. There is a certainty result about the positive relationship between economic growth and carbon emissions depending on the EKC [25][26][27][28][29]. It has been found that the impact of trade liberalization on China's carbon emissions gradually changed over time, from a negative effect to a positive effect [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2018) studied the impact of government governance on regional carbon emissions in China and discovered that the level of legal regulation and regional corruption had a strong negative effect on carbon reduction [22]. There is a certainty result about the positive relationship between economic growth and carbon emissions depending on the EKC [25][26][27][28][29]. It has been found that the impact of trade liberalization on China's carbon emissions gradually changed over time, from a negative effect to a positive effect [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%